A Typology of Political Conditionality Beyond Aid: Conceptual Horizons Based on Lessons from the European Union. (November 2015) - Koch, Svea
Highlights: Tying political conditionality mainly to aid will have little traction. There are now new types and objectives of political conditionality "beyond aid". Research should focus on the interaction and coherence of political conditionality. Summary: This paper asks how political conditionality needs to be conceptualized and researched to reflect global changes. It argues that a diversification of political conditionality "beyond aid" is now taking place. Political conditionality reaches across different external policy fields and includes cooperative and punitive measures. It has also moved from political rights toward social and environmental rights. To capture this diversification conceptually, the article presents an ideal–typical typology that is then refined based on the example of the European Union (EU). A review of the literature on EU political conditionality reveals a gap in studying the interaction of different political conditionality instruments.